A new species of Parakari (Ephemeroptera: Baetidae) from Guiana Highlands - Derka, Tomáš; Nieto, Carolina; Svitok, Marek (Zootaxa, 2015)
The genus Parakari was described from Guiana Highlands in southeastern Venezuela by Nieto & Derka in 2011 for two species inhabiting streams draining isolated, flat-topped table mountains called tepuis. A description of a third representative, Parakari roraimensis sp. n., is given here based on material collected from a coldwater stream at the foothills of Roraima-tepui (SE Venezuela). Detailed morphological descriptions of mature nymph and female adult are given. A differential diagnosis and a key to nymphs of the three Parakari species are provided.